The Effect of Product Innovation, Consumer Awareness, Environmental Policy, Tourist Satisfaction, and Social Culture on Sustainable Tourism in the Tourism Industry in Kintamani Bali - Kurniawan, Ramdhan (Institute for Law and Economics Studies, 2025)
The tourism industry in Kintamani, Bali, is vital for the local economy, offering breathtaking natural attractions such as Mount Batur and Lake Batur. However, rapid tourism growth raises concerns about environmental sustainability and cultural preservation, necessitating a balanced approach to tourism management. This study analyzes factors influencing tourism sustainability in Kintamani, Bali, focusing on product innovation, consumer awareness, environmental policy, tourist satisfaction, and socio-cultural aspects. Using a quantitative method, data were collected via questionnaires from 350-500 domestic and international tourists and analyzed with path analysis. Results show all variables positively and significantly affect tourism sustainability. Product innovation and tourist satisfaction have the greatest impact, followed by environmental policy and socio-cultural aspects. The study highlights the importance of raising tourist awareness about sustainable practices to preserve local nature and culture. Effective environmental policies and community involvement in tourism management are essential for balancing economic growth and ecosystem preservation. Tourism managers are encouraged to develop sustainable innovations, enhance service quality, and enforce environmental policies. Collaboration between government, communities, and tourists is key to maintaining Kintamani as a sustainable destination